2018
DOI: 10.1590/2177-6709.23.2.046-053.oar
|View full text |Cite
|
Sign up to set email alerts
|

Impact of malocclusion on the quality of life of children aged 8 to 10 years

Abstract: Objective: The aim of the present cross-sectional study was to assess the impact of malocclusion on the quality of life of children aged 8 to 10 years attending public elementary schools in Belo Horizonte, State of Minas Gerais, Brazil. Methods: The Brazilian version of the Child Perceptions Questionnaire 8-10 (CPQ8-10) was used to evaluate oral health-related quality of life. The children were examined for the diagnosis of malocclusion using the Dental Aesthetic Index (DAI). The data were analyzed by bivariat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
35
0
11

Year Published

2019
2019
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 53 publications
(48 citation statements)
references
References 19 publications
2
35
0
11
Order By: Relevance
“…Results regarding the change in the overall CPQ [8][9][10] scores of all children of both sexes were statistically significant. This was in agreement with Dutra et al (1) , Piassi et al (5) , Miamoto et al (11) and Abreu et al (20) who concluded that children in the same age group (8 to 10 years) with malocclusions were more likely to have a negative impact on quality of life and that malocclusion treatment reduces that impact and improved quality of life .…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…Results regarding the change in the overall CPQ [8][9][10] scores of all children of both sexes were statistically significant. This was in agreement with Dutra et al (1) , Piassi et al (5) , Miamoto et al (11) and Abreu et al (20) who concluded that children in the same age group (8 to 10 years) with malocclusions were more likely to have a negative impact on quality of life and that malocclusion treatment reduces that impact and improved quality of life .…”
Section: Discussionsupporting
confidence: 90%
“…(22,23) This study was conducted to evaluate the effect of anterior dental crossbite correction on the quality of life in the mixed dentition stage for a group of Egyptian children depending on the hypothesis that anterior crossbite may have a negative effect on patients' quality of life, hindering their social interaction, and affecting their psychological wellbeing. (1,20) Subjects in the current study were chosen to be in the early mixed dentition stage from 8 to 10 years old (with the mean age of (8.63±1.08) because the majority of studies conducted to evaluate the impact of malocclusion on the quality of life for adolescents and young adults (24,25,26,27) and a limited number were carried out in the mixed dentition stage. (28) Since interceptive orthodontic treatment is influenced by ethnic and cultural factors with many several cross-cultural differences in the attitudes and perceptions of patients, (29) this study was carried out on a group of Egyptian children in Fayoum governorate where different cultural factors exist and as such it contributes to the assessment of the burden of malocclusion on the quality of life.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Taibah et al presented that malocclusion has negative effects on self-esteem; multiple malocclusions with spacing, crowding, and overjet had the greatest effects 15 . Studies have presented that adolescents with moderate and severe malocclusion, where the need for treatment was mandatory, experienced a greater negative impact on quality of life [16][17] . However, the patients' perceptions to improve their teeth do not always coincide with the clinicians' view.…”
Section: Discussionmentioning
confidence: 99%
“…1 Mixed dentition is a transitional stage, characterized by a wide range of occlusal variations 2 and a high prevalence of malocclusion. 1,[3][4][5][6][7] In addition, occlusal conditions, such as increased overjet, deep overbite, dental crowding, and spacing, are malocclusions usually associated with dissatisfaction with dental appearance. 4 However, studies addressing the impact of occlusal conditions in the mixed dentition only quantified malocclusion 3,7-9 and did not consider the physiological changes inherent in this stage.…”
Section: Introductionmentioning
confidence: 99%